Normal brain metabolism on FDG PET/MRI during childhood and adolescence. Issue 11 (November 2018) - Barber, Thomas W.; Veysey, Duncan; Billah, Baki; Francis, Peter
Abstract : Objective: The aim was to investigate normal patterns of brain metabolism determined by 18 F-fluorodeoxyglucose positron emission tomography (FDG PET)/MRI during childhood and adolescence. Patients and methods: A retrospective analysis was carried out on all paediatric patients who underwent FDG PET/MRI at our institution between March 2016 and August 2017. Exclusion criteria were neurological disease, central nervous system metastases, previous chemotherapy/radiotherapy, general anaesthesia/sedation and medications suspected to affect cerebral metabolism. Standardized uptake value (SUV)mean and SUVmax were calculated for 12 brain grey matter regions. Subgroup analysis of childhood (⩽10 years old) and adolescence (≥11 years old) was also carried out. Results: From 492 PET/MRI scans, 28 patients (11 children, 17 adolescents) were deemed representative of normal brain metabolism. SUVmean and SUVmax increased with age in all regions. The highest rates of increasing SUVmean were in the thalamus, basal ganglia, frontal lobes, insula and occipital lobes. Higher SUVmean was found in the right frontal, right lateral temporal, right temporal pole, right cingulate/paracingulate, right thalamus, left occipital, left basal ganglia, left insula and left cerebellum compared with the contralateral side. This SUVmean asymmetry was present in both childhood and adolescence in the majority of regions. The highest rates of increasing SUVmax with age were in the occipital lobes, frontal lobes, thalamus and central region. There was no asymmetry in SUVmax in the majority of regions. Conclusion: This FDG PET/MRI study shows that normal brain metabolism measured by SUVmean and SUVmax increases with age in all regions, proceeding at different rates between distinct anatomical sites. Our results suggest that there is mild asymmetry in SUVmean, but mostly symmetric SUVmax during normal development.